Investigation of bridge afflux on channels by experiments and HEC-RAS package - Mohammed Hadi, Arzu; Ardiclioglu, Mehmet (International Journal of Engineering and Technology, 2019)
The bridges are an important part of the transportation network which is constructed over rivers and canals in the urban. The water surface increases upstream of the bridge and constitutes a backwater profile. The maximum afflux and location were investigated via using model test experiments and three different methods by using HEC-RAS package. Laboratory experiments were carried out at ten different flow rates and smooth flow conditions. Measurements and numerical calculations are performed for four different opening ratio M=b/B= 0.3, 0.5, 0.7 and 0.9 where b is the bridge opening and B is the cross-section width. The HEC-RAS package was determined to be closer to the measured values for maximum afflux and wsp (water surface profiles) for large openings. When the opening ratio increases, the distances where maximum affluxes observed also shifted to upstream of the channel.Â Â Â